Suplementação alimentar com óleo de coco virgem previne as alterações na reatividade contrátil e relaxante em traqueia de cobaia submetida à inflamação pulmonar alérgica crônica - Vasconcelos, Luiz Henrique César (2017)
Asthma is a chronic inflammatory disease of the airways characterized by Th2 immune cell infiltrates, bronchial hyperresponsiveness and declining lung function, with many patients failing to respond appropriately to pharmacotherapy. In this sense, aiming to search for an alternative form of antiasthmatic therapy, the possible effects of virgin coconut oil (VCO) on a chronic allergic lung inflammation (CALI) model induced by ovalbumin (OVA) were evaluated. The experimental procedures were approved by the Ethic Committee on Animal Use off UFPB (certificate 0410/13). The animals were divided into control (CG), CALI (ASTG), CALI treated with dexamethasone (2 mg/kg/ day, i.p) (AST/DEXAG) or supplemented with CVO 1 (AST/CO1G), 2 (AST/CO2G) or 4 g/kg/day (p.o) (AST/CO4G). Were analysed the morphology of lung and air tissue, the contractile and relaxing tracheal reactivity, the levels of malondialdehyde (MDA) and the total antioxidant capacity (TAC) in plasma and lung and protein expression in the lung by Western blot. Guinea pigs with CALI exhibited peribronchial inflammatory infiltrate, epithelial hyperplasia and smooth muscle thickening, which were prevented by dexamethasone and VCO. The time for acute response to OVA was also reduced in these animals, being prevented by VCO 4 g/kg. In animals with CALI, trachea contracted in response to OVA administration and was partially prevented by VCO 4 g/kg, indicating an attenuation in the release of contractile mediators. Animals with CALI showed a greater contractile response to carbachol (CCh) and histamine, but not to KCl, in the presence of epithelium, and this response was prevented by dexamethasone and VCO 2 and 4 g/kg for CCh, and 4 g/kg for histamine. The relaxing potency to isoprenaline was reduced, but not to nifedipine, in the presence of epithelium, which was prevented by VCO 4 g/kg, indicating that CALI interfered with the fármaco-, but not the electromechanical coupling of contraction and relaxation, in an epithelium-dependent manner. It was evidenced the participation of of superoxide anion and hydrogen peroxide in the hypercontractility, and the increase on peroxide hydrogen peroxide was prevented by VCO. Also, it was observed that IPAC promoted an increase in releasing 5-lipoxygenase (5-LO) products in CALI, while in AST/CO4G there was a balance between relaxing prostanoids with contractile and the cysteinyl leukotrienes (Cys-LTs). It was also observed a possible increase in activity and/or expression. of inducible NOS (iNOS), but not in endotelial NOS, that wwas prevented by VCO 4 g/kg. Data with the Rho kinase (ROCK) inhibitor suggest an increase in ROCK activity or expression in CALI, which was reverted by VCO. In the investigation of mechanism of relaxant reactivity, it was observed a possible negative modulation of ß receptors/BKCa pathway by TGF-ß, and that VCO prevents only the effects of TGF-ß on ß receptors, but not on the reduction of activity/expression of BKCa. Besides that, CALI appears to increase the Cys-LTs release, that is prevented by VCO. In the analysis of the oxidative stress and antioxidant defenses balance, TAC was reduced in the lungs of animals with CALI, which was reversed only by VCO (2 and 4 g/kg). Finally, the expression of PI3K was increased by CALI, but not ERK1/2 and SOD, and treatment with dexamethasone did not prevent the PI3K increase, but elevated ERK 1/2 levels, and VCO did not prevent the PI3K increase. Therefore, CALI generated peribronchial inflammatory infiltrate, epithelial hyperplasia, smooth muscle thickening and hypercontractility through oxidative stress and its interactions with AA metabolites, the NO, RhoA/ROCK and TGF-ß pathways, and na increase in PI3K expression; and such changes were prevented by virgin coconut oil.